Implementasi Kebijakan Retribusi Pelayanan Pasar Berdasarkan Peraturan Daerah Nomor 1 Tahun 2024 tentang Pajak dan Retribusi Daerah di Kota Gorontalo - Imelda Suma; Asna Aneta; Yacob Noho Nani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Market levies are a regional taxation category that holds significant promise for increasing regional fiscal resources, complementing local tax revenues. The objectives of this study are; (1) Understanding the Communication Mechanism in the Implementation of Market Service Fee Policy in Gorontalo City. (2) Examination of Resource Availability in the Implementation of Market Service Tax Policy in Gorontalo. (3) Understanding the Bureaucratic Framework in the Implementation of Market Service Tax Policy in Gorontalo City. (4) Examination of the Implementation of Market Service Tax Policy Disposition in Gorontalo City. The method used in this study is a descriptive qualitative method. The results of this study indicate that the communication of market service fee policy has been carried out through systematic formal channels and is supported by a clear bureaucratic structure and division of tasks, but its implementation is still not optimal. This is caused by several obstacles, including unequal understanding and distribution of information among traders, limited resources in terms of both quantity and quality of human resources, budget, and inadequate market facilities. Furthermore, weak coordination and suboptimal implementation of SOPs in the field also impact work consistency, while the disposition or attitude of implementers who have demonstrated commitment but are not yet unified requires a more comprehensive strategic approach. Therefore, integrated efforts are needed, including improving the communication framework, strengthening human resource capacity, improving facilities, stricter supervision, and ongoing coaching to create more effective and professional policy implementation.